19th Annual U.C. Berkeley Heavy at Claremont Hotel-Berkeley - Watkins, Howard::::::::: (1987)
David Atkinson, Bill Walker, Denise Morse, Bonnie Neary (pink dress), Jerry Neary, Cathy Barkett, Joe Barkett, Heidi Pieczonka Garofalo (in green dress), Frank Gumpert, Janie Gumpert, and Christine Watkins standing